2003
DOI: 10.1016/s1049-0078(03)00038-1
|View full text |Cite
|
Sign up to set email alerts
|

On the sustainability of current account deficits: evidence from four ASEAN countries

Abstract: This paper examines the sustainability of the current account imbalance for four ASEAN countries (Indonesia, Malaysia, the Philippines and Thailand) over the 1961-1999 period.To this end, we utilize the intertemporal budget constraint (IBC) model to explain the behavior of the current account in these countries. The analysis is based on various unit root and cointegration procedures including those allowing for a structural break to deal with the major shortcomings of previous studies. The empirical results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 47 publications
(44 reference statements)
2
55
0
8
Order By: Relevance
“…The statistical results of the study also lead to the conclusion that Pakistan is not violating its budget constraint. These findings are align with Bahmani-Oskooee and Rhee (1997), Wu and Zhang (1998), Arize (2002), Baharumshah et al (2003), Choong et al (2004), Emmy et al (2009), Irandoust andEricsson (2004), Uddin (2009), andMukhtar andRasheed (2010) but differ from TangTang (2006) , Konya and Singh (2008), Jalil (2008), Dumitriu et al (2009), andHye andSiddiqui (2010). Furthermore, the coefficient of long run relationship between exports and imports estimated by ARDL Model is 0.85196 that indicates that exports do not respond equally to imports, which happens to be one of the major causes of trade deficit in developing countries like Pakistan.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The statistical results of the study also lead to the conclusion that Pakistan is not violating its budget constraint. These findings are align with Bahmani-Oskooee and Rhee (1997), Wu and Zhang (1998), Arize (2002), Baharumshah et al (2003), Choong et al (2004), Emmy et al (2009), Irandoust andEricsson (2004), Uddin (2009), andMukhtar andRasheed (2010) but differ from TangTang (2006) , Konya and Singh (2008), Jalil (2008), Dumitriu et al (2009), andHye andSiddiqui (2010). Furthermore, the coefficient of long run relationship between exports and imports estimated by ARDL Model is 0.85196 that indicates that exports do not respond equally to imports, which happens to be one of the major causes of trade deficit in developing countries like Pakistan.…”
Section: Discussionsupporting
confidence: 84%
“…Statistical results lead to the conclusion that exports and imports do have a long run relationship in case of thirty-five countries and international budget constraints are sustainable for these specific thirty-five countries. Baharumshah et al (2003) found that exports and imports are co-integrated for Indonesia, Philippines, and Thailand by employing co-integration approach on annual data for the period: 1961 to 1999.The same study, by using the same estimation technique and data set concluded that exports and imports of Malaysia are not co-integrated. Contrast to this, another study conducted by Choong et al (2004) found that exports and imports of Malaysia are co-integrated and converge to long run equilibrium and concluded that Malaysia is not violating international budget constraints.…”
Section: Literature Reviewmentioning
confidence: 90%
“…An examination of the data, as well as, our recent research findings on the current account balances of the severely crisis-affected countries indicates that the current account swung from a large deficit to surplus after the currencies of these countries took a sharp fall. Indeed, the study by Baharumshah et al (2003) shows that after the crisis all the crisis-affected East Asia countries maintained current accounts that are sustainable. The sensitivity of the cointegration results to the regime that was noted above carries the policy implication that the exchange rates of the East Asia countries were possibly misaligned, i.e., overvalued, during the pre-crisis period.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Arize (2002) explained that cointegration between exports and imports is an important element for formulating macroeconomic policies intended to achieve trade balance. Baharumshah et al (2003) got existence of cointegrating relationship between imports and exports for Indonesia, Philippines, Thailand, but not for Malaysia.…”
Section: Introductionmentioning
confidence: 99%